Electrocatalytic assisted one pot three component reaction for construction of highly substituted pyridine. (Indian Journal of Chemistry (IJC), 2025)
An electrochemically environmentally benign synthetic strategy has been developed for substituted pyridine by condensation of structurally diverse aldehydes with various thiols and malononitrile.